Palladacycle-catalyzed asymmetric hydrophosphination of achiral heterobicyclic alkenes - Ong, Yew Jin (2018)
Palladacycle-catalyzed asymmetric hydrophosphination of achiral heterobicyclic alkenes offers an unprecedented access towards novel chiral phosphine motifs. As an expansion of the substrate scope, four substrates that represent oxygen, nitrogen and carbon-bridged bicyclic alkenes were examined for their compatibility with this approach. Only one enantioenriched product was obtained with a moderate enantiomeric excess of 56%.